2022
DOI: 10.3390/nano12020226
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnologies in Delivery of DNA and mRNA Vaccines to the Nasal and Pulmonary Mucosa

Abstract: Recent advancements in the field of in vitro transcribed mRNA (IVT-mRNA) vaccination have attracted considerable attention to such vaccination as a cutting-edge technique against infectious diseases including COVID-19 caused by SARS-CoV-2. While numerous pathogens infect the host through the respiratory mucosa, conventional parenterally administered vaccines are unable to induce protective immunity at mucosal surfaces. Mucosal immunization enables the induction of both mucosal and systemic immunity, efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 211 publications
(250 reference statements)
0
26
0
Order By: Relevance
“…A previous report of self-amplifying RNA delivery by the IN route using multiple delivery systems including LNPs showed poor immunogenicity relative to more typical IM or intradermal injections, and was associated with rapid clearance (56). For the most part, intranasal delivery of mRNA vaccines have been attempted using well-established polymer-based transfection reagents, though such polymer-based approaches have not historically reached clinical application successfully, possibly in part due to toxicity issues (57)(58)(59)(60). Moreover, IN LNP can induce lethal inflammatory responses in mice, complicating studies of alternative administration routes (48).…”
Section: Discussionmentioning
confidence: 99%
“…A previous report of self-amplifying RNA delivery by the IN route using multiple delivery systems including LNPs showed poor immunogenicity relative to more typical IM or intradermal injections, and was associated with rapid clearance (56). For the most part, intranasal delivery of mRNA vaccines have been attempted using well-established polymer-based transfection reagents, though such polymer-based approaches have not historically reached clinical application successfully, possibly in part due to toxicity issues (57)(58)(59)(60). Moreover, IN LNP can induce lethal inflammatory responses in mice, complicating studies of alternative administration routes (48).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from both our group and others have clearly demonstrated that poloxamine-based delivery system mediates significantly better levels of DNA transfection and lower levels of associated inflammatory response in the airways of mouse and pig models than were achieved with the cutting-edge lipid-based formulations 26, 32, 33 . PEI was adopted as a control formulation because it is one of the most well-studied polymer-based gene carrier and has been applied in many mucosal DNA vaccine applications 43 . Although PEI appears to be promising in delivery of mucosal DNA vaccines encoding antigens of Influenza, HIV and SARS-CoV 43 , we found it fails to mediate efficient DNA transfection in the mouse airway, perhaps owing to its poor mucus penetrating properties.…”
Section: Discussionmentioning
confidence: 99%
“…PEI was adopted as a control formulation because it is one of the most well-studied polymer-based gene carrier and has been applied in many mucosal DNA vaccine applications 43 . Although PEI appears to be promising in delivery of mucosal DNA vaccines encoding antigens of Influenza, HIV and SARS-CoV 43 , we found it fails to mediate efficient DNA transfection in the mouse airway, perhaps owing to its poor mucus penetrating properties. We applied an improved method of preparing nanoparticles without aggregation to enhance the utility of PP-sNp for in vivo applications 44 .…”
Section: Discussionmentioning
confidence: 99%
“…It is an inexpensive, inert, harmless, fire-resistant, and environmentally friendly approach, in which atomized water droplets are used to coat phospholipid vesicles under high diffusion of carbon dioxide. In this, size and shape can be controlled precisely [ 147 , 148 ]. Cholecalciferol-loaded nanoliposomes were prepared with this approach and 66.7 to 88.9% encapsulation efficiency has been achieved [ 149 ].…”
Section: Challenges and Future Prospectivesmentioning
confidence: 99%